Estudo termoambiental em viaturas utilizadas nos serviços de radiopatrulhamento no estado da Paraíba - Medeiros, Elaine Gonçalves Soares de (2014)
One increasingly common workplace in the twenty-first century is the automobile. It is used to realize the activity of car patrolling by the Military Police. Being the state of Paraíba in a tropical and semi-arid climate, considering the standard uniform used by the police for the activity concerned, besides the instruments needed for the activity, ratings related to thermal comfort of officers on the car patrolling activity becomes summary, being this the objective of this study. For this purpose the following standards were applied: ISO 14505 (2007): Ergonomics of the thermal environment - Evaluation of thermal environments in vehicles, ISO 7243 (1989): Hot environments - Estimation of the heat stress on working man, based on the WBTG-index and ISO 7933 (1989): Hot environments - Analytical determination and interpretation of thermal stress using calculation of required sweat rate. The results showed that all the parameters considered in ISO 14505-3 (2006) showed the thermal environment as uncomfortable. Moreover, after correction of the thermal insulation factor for the WBGT index, considering a ̅̅̅̅̅̅̅̅̅ = 27.88 º C it is determined that the activities under study can not be performed without precautionary steps to be taken. Still, the required sweating rate was below the maximum allowed, however, the fraction of required wet skin (wreq) is equal to the fraction of maximum wet skin (wmax), exposing the subjects to the danger. Thus, it is noticed that among the studied parameters, the activity of car patrolling performed by the Military Police of the 1st Battalion of Paraíba is considered inadequate in relation to the thermal parameters.